ANALISIS TINGKAT KERUSAKAN GEDUNG PADA KOMPLEK PERKANTORAN KANTOR BUPATI KUTAI KARTANEGARA - Andi Aqsar Hamzah; Eswan, Eswan; Wahyu Mahendra Trias Admaja (LPSDI Bina Patria, 2025)
Building D is one of the buildings in the Office Complex of the Kutai Kartanegara Regent's Office. Over time the building will experience degradation. This will result in initial damage, so an inspection of the building condition is required. The results of the inspection with the visual inspection method of damage resulted in a damage value level of 20.32%, including the category of minor damage, while the test results with the Non Destructive Test (NDT) method are more structural in nature, where the test results with the Hammer Test resulted in a minimum compressive strength value of 17 Mpa in accordance with SNI standards regarding structural concrete requirements. For testing with UPV, it produces a wave velocity value of 3513 m/sec, which indicates the homogeneity of concrete is still quite good, while the results of the Rebar Scanner show that the dimensions of the reinforcement and the distance between the reinforcement are in accordance with the planning design and structural design standards